Hayaang samahan ka ng kalusugan - Hong, Zhaoguang 1939-; Sy, Joaquin ([Manila, Philippines] Neomakers International, 2004)
Tips on health.
Parallel title on cover in Chinese characters.
In Tagalog.
Keywords: Medicine, Popular